1992
DOI: 10.1002/ana.410310610
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging in temporal lobe epilepsy: Relationship to neuropathology and neuropsychological function

Abstract: Magnetic resonance images (MRIs) were obtained from 25 patients with medically refractory epilepsy of temporal lobe origin (12 on the left, 13 on the right) and 14 right-handed control subjects. The hippocampi and temporal lobes were traced by computer on successive coronal images and the resulting measurements of area were summed for each region. The left and right hippocampi were symmetrical in the control subjects; however, for patients the hippocampus was smaller on the side of the seizure focus. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
174
3
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(191 citation statements)
references
References 34 publications
12
174
3
2
Order By: Relevance
“…Overall, thalamic volume was a stronger correlate of both memory and nonmemory cognitive functioning than hippocampal volume. Similar to several other reports, a smaller left hippocampus was significantly associated with poorer verbal memory performance and hippocampal volume in the right TLE group did not show any significant association with cognition (Bonilha et al, 2007;Griffith et al, 2004;Lencz et al, 1992;Rausch et al, 1994). However, hippocampal volume (either left or right) was not significantly correlated with the nonmemory neuropsychological indices.…”
Section: Cognitive Functioningsupporting
confidence: 87%
“…Overall, thalamic volume was a stronger correlate of both memory and nonmemory cognitive functioning than hippocampal volume. Similar to several other reports, a smaller left hippocampus was significantly associated with poorer verbal memory performance and hippocampal volume in the right TLE group did not show any significant association with cognition (Bonilha et al, 2007;Griffith et al, 2004;Lencz et al, 1992;Rausch et al, 1994). However, hippocampal volume (either left or right) was not significantly correlated with the nonmemory neuropsychological indices.…”
Section: Cognitive Functioningsupporting
confidence: 87%
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 67%
“…It has been proposed that FDG-PET hypometabolism is closely associated with the presence of underlying MTS and correlates with the degree of hippocampal volume loss measured by means of volumetric MRI (8,9,26). Conversely, several studies failed to show a clear relation between hippocampal neuronal cell loss, which is correlated with hippocampal atrophy, and interictal FDG-PET hypometabolism (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%